Neonational-Developmentalism and Class Relations during the Lula Governments - Almeida, Lúcio Flávio Rodrigues de (Pontifícia Universidade Católica de São Paulo, 2015)
The studies on class relations and State policy during the Lula governments have grown exponentially and are a long way from being consensual. The objective of this article is to highlight some of the main theoretical-political questions in play and to briefly propose some hypotheses on this debate, beginning with the very notion of development.